Low Poly Modelling Planet Pada Film Animasi Gerhana Bulan dan Gerhana Matahari - Ramadhanty, Viga Sakina; Lubis, Imran; Budiman, Arief (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2022)
This study aims to design and build the process of the occurrence of a lunar eclipse and a solar eclipse in the form of 3-dimensional animation. This process provides information about how lunar and solar eclipses occur using low poly modeling techniques. This technique is used so that the rendering process does not take a long time and also displays a unique object shape because of the large number of polygons formed. Animations were created using blender software version 2.92 and editing using adobe premiere pro software. The results of this study are implemented in the form of animated films that can be opened via mobile phones or laptops. Keywords: 3D animation, low poly modelling, polygon, software blender version 2.92, software adobe premiere pro.